Total Cross Sections for Electron Scattering from $CF_4$, $C_2F_4$, $C_2F_6$, $C_3F_8$ in the Energy Range from 100 eV to 5000 eV (Journal of Atomic and Molecular Sciences, 2015)
The additivity rule for electron scattering from molecule has been revised byconsidering the difference between the free atom and the corresponding bound atomin the molecule. The total cross sections for electron scattering from plasma etchingmolecules $CF_4,$ $C_2F_4,$ $C_2F_6$ and $C_3F_8$ have been calculated in the energy range from 100eV to 5000 eV with the revised additivity rule. The present calculations are comparedwith the original additivity rule results and the existing experimental data. A betteragreement between the present results and the experimental data is obtained.
Keywords: total cross section; electron scattering; the revised additivity rule.